Complications of Endoscopic Examination in Patients at Idris Teaching Hospital Sialkot (Medical Forum Monthly, 2020)
Objective: To study Complications Of Endoscopic Examination In Patients At Idris Teaching Hospital Sialkot.Study Design: Experimental and observational studyPlace and Duration of Study: This study was conducted at the Idris Teaching Hospital Sialkot during Jan 2018 to July 2019.Materials and Methods: This study comprises 1021 patients undergoing endoscopic examination. The demographic data and complications during endoscopic examination were noted down and lab tests were also advised for example hepatitis A , B and C HIV. Written informed consent was also taken from every patient before the start of the endoscopic examination . The Permission of ethical committee was also considered before collection of data and get publishing in the medical journal. The results were analyzed on SPSS version 10.Results: Mean Age was 45.34 years and SD(standard deviation) was 16.23 years. At the age of 10-20years , there were 50(10.18%) male and 51(9.62%) female of endoscopy were included in this study. At the age of 21-30 years there were 101(20.57%) male and 85(16.04%) females. At the age of 31-40 years there were 100(20.36%) male and 75(14.15%) female, At the age of 41-50 years there were 101(20.57%) male and 130(24.52%) female , at the age of 51-60 years there were 25(5.09%)Male and 75(14.15%) female. At the age of 61-70 years there were 75 (15.27%) male and 85(16.04%) female, at the age 70 years and above there were 35(7.12%) Male and 29(5.47%) females patients were included in the study. It was observed that female patients of endoscopy were more prevalence than male patients. There were 17(3.46%) Male and 15(2.83%) female patients were found in bleeding during endoscopic examination , the perforation was found in 07 (1.42%) Male and 06(1.13%) Females. The hepatitis A 15(3.05%) Male and 07(1.32%) Female, the hepatitis B 13(2.64%)Male and 03(0.56%) females, the hepatitis C were 18(3.66%) Male and 13(2.45%) female and HIV 02(0.41%) male and 00(00%) female patients.Conclusion: Endonasal endoscopy without stent is considered as effective, safe and minimally invasive primary procedure for the treatment of nasolacrimal duct obstruction. This procedure has fewer complications and is well tolerated by the patient. In this procedure there is minimum damage to anatomical structures. Mutual efforts by Ophthalmologists and Otorhinologist made endonasal DCR a good alternative to external DCR with high success rate and comparable outcomes. Regular follow up are required to evaluate the process of wound healing and early detection of complications leading to failure of the procedure.